Analisis Perencanaan Capacitor Bank Untuk Perbaikan Faktor Daya Pada Pusat Perbelanjaan Blitar Square - Sulistyowati; Muhammad Fahmi Hakim; Ikfi Asmaul Khusna; Heri Sungkowo (Elposys: Jurnal Sistem Kelistrikan, 2021)
From the research that has been done at the Blitar Square Shopping Center, it was found that the power factor value is still below the standard with an average value of 0.711. Therefore, it is necessary to improve the power factor by installing a capacitor bank. The calculation results show that global compensation requires 12 capacitor banks with a rating of 10.4 kVAR, while sectoral compensation on the chiller load panel requires 7 capacitor banks with a rating of 10.4 kVAR and the foodmart load panel requires a capacitor bank with a rating of 10. 4 kVAR is 6 pieces. In addition, the installation of a capacitor bank also results in an increase in the voltage value in the system, this voltage increase is still below the permissible standard of ± 5%. The simulation of installing a capacitor bank on global compensation can improve the power factor value from 72.99% to 96.97%, with a voltage increase of 0.479% from the initial value of 397 V to 398.9 V, and a decrease in the current value of 24.645% from the initial value. 330.7 A to 249.2 A. While the simulation of installing a capacitor bank in sectoral compensation can improve the power factor value from 72.99% to 93.57%, with a voltage increase of 0.401% from the initial value of 397 V to 398.6 V , and a decrease in the value of current by 21.593% from the initial value of 330.7 A to 258.1 A.